2018
DOI: 10.1055/s-0038-1676538
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Lower Extremity Reconstruction: Evaluating Body Mass Index as an Independent Risk Factor for Early Complications

Abstract: Background The prevalence of obesity in the United States continues to grow and is estimated to affect over a quarter of the working-age population. Some studies have identified obesity as a risk factor for flap failure and complications in free flap-based breast reconstruction, but its clinical significance is less clear in nonbreast reconstruction. The role of obesity as a risk factor for failure and complications following lower extremity reconstruction has not been well described, and the limited existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…65 Additionally, many studies have documented obesity's role in increasing arterial caliber in response to the increased perfusion and nutrient needs of the larger tissue mass. [66][67][68][69][70] While imaging studies of deep inferior epigastric artery perforators have not found universal increases in perforator diameter among obese patients, [70][71][72] anecdotal intraoperative observations continue to support this in many reports. 55,59,70 Furthermore, other studies have suggested that obstetric and gynecologic procedures may also increase the quantity of visualized perforators via the surgical delay phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Additionally, many studies have documented obesity's role in increasing arterial caliber in response to the increased perfusion and nutrient needs of the larger tissue mass. [66][67][68][69][70] While imaging studies of deep inferior epigastric artery perforators have not found universal increases in perforator diameter among obese patients, [70][71][72] anecdotal intraoperative observations continue to support this in many reports. 55,59,70 Furthermore, other studies have suggested that obstetric and gynecologic procedures may also increase the quantity of visualized perforators via the surgical delay phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…76 The latter compounds the risk for kidney injury when also considering the significant impact of obesity in the development of renal disease and metabolic syndrome. 69,76,77 Patient access and positioning can also constrain imaging protocol if there exists a mismatch between patient size and the specifications of the CT machine. 76 Additionally, DelMauro and Moon recently observed fewer major deep inferior epigastric artery perforators among patients with higher BMIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of lower extremity reconstruction with free tissue transfer, obesity has not been demonstrated to affect overall outcomes. 31,32 While the data on obesity is mixed, malnutrition, a common problem in head and neck reconstruction population, has been shown to have significant association with flap failure whether it is related to wound healing or vascular anastomosis problems. [33][34][35] The evaluation of the patient's nutritional status is a critical part of their preoperative evaluation.…”
Section: Preoperative Considerations Patient Selectionmentioning
confidence: 99%